Identification of Peanut AhMYB44 Transcription Factors and Their Multiple Roles in Drought Stress Responses - Yonghui Liu; Yue Shen; Man Liang; Xuyao Zhang; Jianwen Xu; Yi Shen; Zhide Chen (Plants, 2022)
MYB transcription factors (TFs) comprise a large gene family that plays an important role in plant growth, development, stress responses, and defense regulation. However, their functions in peanut remain to be further elucidated. Here, we identified six AhMYB44 genes (AhMYB44-01/11, AhMYB44-05/15, and AhMYB44-06/16) in cultivated peanut. They are typical R2R3-MYB TFs and have many similarities but different expression patterns in response to drought stress, suggesting different functions under drought stress. Homologous genes with higher expression in each pair were selected for further study. All of them were nuclear proteins and had no self-transactivation activity. In addition, we compared the performances of different lines at germination, seedling, and adult stages under drought stress. After drought treatment, the overexpression of AhMYB44-11 transgenic plants resulted in the longest root length at the seedling stage. Levels of proline, soluble sugar and chlorophyll, and expression levels of stress-related genes, including P5CS1, RD29A, CBF1, and COR15A, were higher than those of the wild type (WT) at the adult stage. While the overexpression of AhMYB44-16 significantly increased the drought sensitivity of plants at all stages, with differential ABA content, the expression levels of the ABA-related genes PP2CA and ABI1 were significantly upregulated and those of ABA1 and ABA2 were significantly downregulated compared with the WT. AhMYB44-05 showed similar downregulated expression as AhMYB44-16 under drought stress, but its overexpression in Arabidopsis did not significantly affect the drought resistance of transgenic plants. Based on the results, we propose that AhMYB44-11 plays a role as a positive factor in drought tolerance by increasing the transcription abundance of stress-related genes and the accumulation of osmolytes, while AhMYB44-16 negatively regulates drought tolerance through its involvement in ABA-dependent stress response pathways.